Features of spleen morphology in fish - Kot, T.; Kovalchuk, V. (Scientific Progress & Innovations, 2025)
The spleen refers to the peripheral organs of hematopoiesis and immune protection of fish. it performs depository, hematopoietic, immune and filtration functions. One of the most pressing problems of ichthyomorphology, veterinary and fish farming practice is the study of the structure of the spleen at the macro- and microscopic level. However, modern studies on the morphology of the spleen of fish are mainly devoted to the features of pathological changes in infectious and invasive diseases, with the influence of unfavorable factors of the natural environment, conditions of maintenance, and anthropogenic load. The purpose of the work is to conduct a scientific review to study the morphology of the spleen of fish in normal condition. Electronic search for publications has been conducted in the web of Science, Scopus, PubMed, and Google Scholar databases, mainly over the past 20 years. The principles of objectivity and a comprehensive attitude to the study of the chosen problem are used. The authors of the review article reviewed modern scientific literature and summarized current knowledge on the peculiarities of spleen morphology in fish. the anatomical structure of the fish spleen is presented with an emphasis on its topography, shape, color, weight and size. According to the description of the microscopic structure of the fish spleen, the main structural components of its stroma and parenchyma are characterized. The microscopic structure of the capsule and trabeculae of the spleen stroma is presented, which, according to modern morphological studies, together with the reticular framework of the red pulp, lymphoid nodes and vaginal membranes of the vessels, belong to the musculoskeletal apparatus of the spleen. Microscopic structure of structural components of the white pulp of the spleen (lymphoid nodules, periarterial lymphoid vaginas, perielipsoid lymphoid vaginas or ellipsoids) with analysis of their morphometric parameters is described. Features of the bloodstream (arterioles, capillaries, venous sinuses or sinusoids) are presented by describing the structure of the red pulp of the spleen. Information about the microscopic structure and specifics of the placement of melanoma-macrophage centers in the parenchyma of the fish spleen is detailed. in general, the presented anatomical features of the fish spleen are relevant for the comparative anatomy of fish of different classes. Data on the microscopic structure of structural components of white and red fish spleen pulp are of practical importance for assessing the morphofunctional state of fish, which is important for scientific justification of fish growth technologies and mastering the mechanisms of development of spleen diseases. Morphometric parameters of the spleen can serve as a theoretical basis for developing a normal spleen test system to detect morphometric changes due to environmental factors.